2006
DOI: 10.1038/sj.hdy.6800901
|View full text |Cite
|
Sign up to set email alerts
|

The recent demographic and adaptive history of Drosophila melanogaster

Abstract: Population genetic analyses of the past two decades confirmed an earlier hypothesis by L Tsacas and D Lachaise that the cosmopolitan species Drosophila melanogaster has an Afrotropical origin, and that it colonized the rest of the world only very recently. Maximum likelihood analyses based on multilocus data suggest that the putative ancestral African population expanded its size about 60 000 years ago (ya). These demographic changes were accompanied by the fixation of numerous beneficial mutations, as reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
98
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 30 publications
(52 reference statements)
6
98
1
Order By: Relevance
“…Thus, if one rejects neutrality, this could be due to a selective sweep, but it could also be due to the fact that the demographic history of the population is not approximated well by the SNM. This is a serious practical concern because many populations of humans, Drosophila, and domesticated species have demographic histories that are far more complex than allowed for by the SNM (Wright et al 2005; Thornton and Andolfatto 2006;Stephan and Li 2007;Gutenkunst et al 2009;Lohmueller et al 2009;Wall et al 2009;vonHoldt et al 2010). One strategy that has been widely employed to deal with the problem of demography is to use a more realistic demographic model to define the critical values of the standard tests of neutrality (Akey et al 2004;Wright et al 2005;Li and Stephan 2006; Thornton and Andolfatto 2006;Nielsen et al 2009).…”
Section: T He Classic Model Of Genetic Hitchhiking Predictsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if one rejects neutrality, this could be due to a selective sweep, but it could also be due to the fact that the demographic history of the population is not approximated well by the SNM. This is a serious practical concern because many populations of humans, Drosophila, and domesticated species have demographic histories that are far more complex than allowed for by the SNM (Wright et al 2005; Thornton and Andolfatto 2006;Stephan and Li 2007;Gutenkunst et al 2009;Lohmueller et al 2009;Wall et al 2009;vonHoldt et al 2010). One strategy that has been widely employed to deal with the problem of demography is to use a more realistic demographic model to define the critical values of the standard tests of neutrality (Akey et al 2004;Wright et al 2005;Li and Stephan 2006; Thornton and Andolfatto 2006;Nielsen et al 2009).…”
Section: T He Classic Model Of Genetic Hitchhiking Predictsmentioning
confidence: 99%
“…The idea that genetic hitchhiking distorts patterns of genetic variation has been used to derive several statistical tests to evaluate whether one can reject the SNM for a particular region of the genome. Many recent studies have applied tests of neutrality to data from humans (reviewed in Nielsen et al 2007), Drosophila (reviewed in Stephan and Li 2007;, and domestic dogs (Pollinger et al 2005;Akey et al 2010;Boyko et al 2010) to locate regions of the genome that have evolved under natural selection. These signatures have been used to detect the footprints of recent selection (reviewed in Nielsen 2005).…”
Section: T He Classic Model Of Genetic Hitchhiking Predictsmentioning
confidence: 99%
“…Although it is clear that presumably ancestral East African populations (Pool and Aquadro 2006) show strong signals of nonequilibrium demography (for review see Stephan and Li 2007), it has mostly been assumed that many of the observed deviations from neutrality have been driven by population expansion (although see Haddrill et al 2005). As a consequence, the parameter space for characterizing the demographic history of African populations has not been thoroughly explored.…”
mentioning
confidence: 99%
“…Many sophisticated methodologies for estimating demographic parameters have been developed, and application of such methods has revealed much about the demographic history of natural populations of D. melanogaster (Haddrill et al 2005;Ometto et al 2005; Thornton and Andolfatto 2006;Stephan and Li 2007;Laurent et al 2011). Although it is clear that presumably ancestral East African populations (Pool and Aquadro 2006) show strong signals of nonequilibrium demography (for review see Stephan and Li 2007), it has mostly been assumed that many of the observed deviations from neutrality have been driven by population expansion (although see Haddrill et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation